Proceso de ASC - ESTUDIO E IMPLEMENTACION DE UN SISTEMA CAPAZ DE DETECTAR LAS SEÑALES DE RADIO EMITIDAS POR LA TRAZA DE METEOROS (2022)
The remnants of the formation of the solar system left, among other stellar objects, small remnants commonly known as shooting stars. Observing these objects is difficult because ideal weather conditions are required. Therefore, this report proposes the preliminary design of a radio detection device to identify these meteor showers. This will involve several phases, including a review of the literature on the physical aspects and the necessary instrumentation for the setup, concluding with a study of the data collected through radio detection.